Effect of iron oxide content and microstructural porosity on the performance of ceramic membranes as microbial fuel cell separators. (20th January 2021) - Salar-García, M.J.; Walter, X.A.; Gurauskis, J.; de Ramón Fernández, A.; Ieropoulos, I.
Highlights: Suitable bioelectrochemical application of ceramic clays with varying Fe2O3 content. 5.75% of Fe2O3 and 1100 °C of sintering temperature allow MFCs to reach 1.045 mW. The Fe2O3 content mitigates the effect of porosity features on the MFC power output. Good stability of the MFCs working during 65 days in continuous mode. Abstract: Ceramic materials based on naturally occurring clays are a low cost and environmentally friendly alternative to commercial polymer-based membranes in bioelectrochemical systems. In this work, ceramic membranes containing different amounts of iron oxide (1.06, 2.76 and 5.75 vol.%) and sintered at different temperatures (1100, 1200 and 1300 °C) have been elaborated and tested as separators in urine-fed microbial fuel cells (MFCs). The results reveal that the presence of iron oxide in the ceramic membrane composition increases the structural porosity and reduces the pore size for the three temperatures investigated. On the other hand, it was also observed that the iron content mitigates the negative effect of the high sintering temperature on the power performance of the MFCs. In the case of the ceramic membranes sintered at 1300 °C, power output improved ca. 10-fold when the iron oxide content in the membrane increased from 1.06 up to 5.75 vol.% (30.9 and 286.6 µW, respectively). Amongst the different combinations of iron phase content and sintering temperatures, the maximum power output was obtained by MFCs working with separators containing 5.75 vol. % of iron oxide and sintered at 1100 °C (1.045 mW). Finally, the system was stable for 65 days, which supports the long-term functionality of the different materials assessed.